New distributional records of Staphylinina in Taiwan, including a new species of Miobdelus Sharp (Coleoptera: Staphylinidae: Staphylininae: Staphylinini) - Hu, Fang-Shuo (Zootaxa, 2020)
Miobdelus humilis sp. nov. is described as new. A lectotype is designated for Staphylinus (Xanthocypus) miwai Bernhauer, 1943 and Thoracostrongylus miyakei Bernhauer, 1943. Ocypus (Ocypus) miwai (Bernhauer, 1943) is transferred from Ocypus Leach, 1819 to Sphaerobulbus Smetana, 2003 and the species is re-described based on types and modern specimens. A female description of Apecholinus imitator Smetana & Hu, 2019 is provided. Creophilus flavipennis Hope, 1831, Nelmanwaslus ornatus Smetana, 2006, Ontholestes oculatus (Sharp, 1874) and Platydracus juang Smetana, 2005 are reported for the first time from Taiwan. Ontholestes oculatus is re-described based on Taiwanese material, representing the first record of the genus Ontholestes Ganglbauer, 1895 in Taiwan. Platydracus juang is considered to be a termitophilous species, associated with Reticulitermes leptomandibularis (Hsia & Fan, 1965), which would represent the first report of termitophily in the subtribe Staphylinina. Additional records of C. maxillosus maxillosus (Linnaeus, 1758), Agelosus auricomus Smetana & Hu, 2019, Apecholinus fraternus Fairmaire, 1891, Miobdelus taiwanensis taiwanensis Smetana, 2001, Naddia taiwanensis Shibata, 1979 and Thoracostrongylus formosanus Shibata, 1982 are provided. Habitus photos of the above species and Dinothenarus choui Smetana, 1992 are also provided. A preliminary checklist of Staphylinina in Taiwan is proposed.